Hormonal contraception in thrombophilic adolescents - Rott, H. (Hämostaseologie, 2012)
About 3.2 million women in Germany are between 14 and 19 years old representing about 19% of women. 55% of them use combined oral contraception (COC). The risk of venous thromboembolism (VTE) during the use of COC is increased 2–6 times. For thrombophilic patients depending on the kind of thrombophilic defect it is much higher. Pregnancy and postpartum period lead to a much higher increase of VTE than any COC use at all, both in women with and without thrombophilic defect. VTE risk in COC is highly dependent on the content of ethinylestradiol (EE) and the kind of progestagen used in COC. Progestagen-only contraceptives (POC) do not increase the VTE risk, since they do not activate the coagulation system. Conclusion: It is not justified to withhold any hormonal contraception to thrombophilic women, especially considering the much higher VTE risk in (maybe unintended) pregnancy. Adolescents thrombophilic women should rather be informed about the opportunity to use POC.
Keywords: Thrombophilia; contraception; adolescents; COC; progestagen only pills